2002
DOI: 10.1007/s005950200047
|View full text |Cite
|
Sign up to set email alerts
|

Monocyte Chemoattractant Protein-1 Expression in Intimal Hyperplasia of Vein Grafts in a Rat Model

Abstract: These results show that there could be a direct correlation between the significant increases in MCP-1 mRNA expression, Mo/Mphi infiltration, and the development of IH in vein grafts, not seen in FA anastomoses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 16 publications
0
7
0
Order By: Relevance
“…Recently we compared rat interposition vein grafts and in situ artery grafts. Then we found IH becomes significantly larger after two weeks in vein graft, and the expression of MCP-1 rnRNA is also significantly increased in vein graft by one day [6]. In this study we have analyzed that serum MCP-1 levels already start to increase just after bypass (0 hour).…”
Section: Discussionmentioning
confidence: 80%
See 2 more Smart Citations
“…Recently we compared rat interposition vein grafts and in situ artery grafts. Then we found IH becomes significantly larger after two weeks in vein graft, and the expression of MCP-1 rnRNA is also significantly increased in vein graft by one day [6]. In this study we have analyzed that serum MCP-1 levels already start to increase just after bypass (0 hour).…”
Section: Discussionmentioning
confidence: 80%
“…Although we found the expression of MCP-I mRNA is also significantly increased in vein graft [6], in this study we have analyzed that serum MCP-1 levels of vein graft. The advantage of serum MCP-1 levels is that it is so easy to sample, that clinically it may be more useful in near future.…”
Section: Study Limitationsmentioning
confidence: 85%
See 1 more Smart Citation
“…1. 5 My research showed that endothelial injury and monocyte infiltration are the key to postoperative intimal hyperplasia, 5,6 which is very similar to the pathogenesis of atherosclerosis as an inflammatory disease "response-to-injury hypothesis" proposed by R. Ross, 7 except for the lack of smooth muscle proliferation in vein (►Fig. 2).…”
mentioning
confidence: 70%
“…3 After my vascular surgery residency in Japan, I started my research work on postoperative intimal hyperplasia at the University of Wisconsin-Madison. 4 The postoperative view under the microscope is shown in ►Fig. 1.…”
mentioning
confidence: 99%